Efficacy and tolerance of early administration of tranexamic acid in patients with cirrhosis presenting with acute upper gastrointestinal bleeding: a study protocol for a multicentre, randomised, double-blind, placebo-controlled trial (the EXARHOSE study). Issue 8 (10th August 2018) - Heidet, Matthieu; Amathieu, Roland; Audureau, Etienne; Augusto, Oriane; Nicolazo de Barmon, Violaine; Rialland, Amandine; Schmitz, David; Pierrang, François; Marty, Jean; Chollet-Xémard, Charlotte; Thirion, Olivier; Jacob, Line
Abstract : Introduction: The management of acute upper gastrointestinal bleeding (UGIB) is challenging in patients with cirrhosis, as it is responsible for severe complications and high mortality rates. Tranexamic acid (TXA) may help control the bleeding by counterbalancing cirrhosis-related hyperfibrinolysis. Still, there is a lack of unbiased data to conclude on its efficacy. The aim of this study is to evaluate the efficacy of TXA in the early treatment of acute UGIB in patients with cirrhosis. Methods and analysis: This study is a multicentre, randomised, double-blind, placebo-controlled trial, for adult patients with cirrhosis presenting with an acute UGIB and allocated to one of two arms: TXA or placebo (saline). Physicians from emergency mobile services, emergency departments (EDs) or intensive care units (ICUs) can include patients. Besides study intervention, standard care for UGIB will be performed as recommended. Intervention will consist an intravenous infusion of 10 mL of TXA (1 g) or saline, immediately followed by three identical intravenous infusions over 8 hours each (total dose of 4 g of TXA or 40 mL of placebo over 24 hours). Main analyses will be conducted in intention to treat on every patient included, then in modified intention to treat on patients with underlying lesion of portal hypertension visualised by endoscopy. The main objective is to show efficacy of TXA until day 5 on a composite criterion (bleeding control, rebleeding episodes and mortality). Secondary objectives aim at showing the efficacy of TXA on each individual component of the main outcome measure and others at 6 weeks and later (transjugular intrahepatic portosystemic shunt procedure, cirrhosis-specific complications, length of stay in ICU and in hospital, safety and tolerance of TXA, liver transplantation). Included patients will be followed up to 1 year after inclusion. 500 patients will be necessary to show a reduction in the prevalence of the primary outcome from 30% to 18% with a bilateral alpha risk of 5% and a power of 80%. Ethics and dissemination: Ethical approval has been obtained from the Comité de Protection des Personnes Ile-de-France 1 (CPP-IDF1). Results will be disseminated via publications in peer-review medical journals and scientific forums. Protocol version: This protocol is based on the latest version, as established on 11 October 2017 and validated by the IRB CPP Ile-de-France 1. Trial registration number: NCT03023189 .